2010
DOI: 10.1510/icvts.2009.216408
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac troponin I levels after cardiac surgery as predictor for in-hospital mortality☆

Abstract: Postoperative cTnI level, measured within the first hour after cardiac surgery, can identify a subgroup of patients with increased risk for hospital mortality. These patients may benefit from better monitoring, eventually with specific diagnostic and therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Cardiac Troponin I (cTnI) was defined as a marker of myocardial injury, which has reported to be superior insensitivity and specificity when compared with habitual biomarkers, such as creatine kinase and myoglobin [19]. However, it can be affected by the iatrogenic stressors of CABG and is not typically associated with permanent myocardial injury [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac Troponin I (cTnI) was defined as a marker of myocardial injury, which has reported to be superior insensitivity and specificity when compared with habitual biomarkers, such as creatine kinase and myoglobin [19]. However, it can be affected by the iatrogenic stressors of CABG and is not typically associated with permanent myocardial injury [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Salamonsen et al suggested that a single cTnI measurement 24 hours after CABG can be beneficial for identifying adverse outcomes with high efficacy and simplicity [21]. van Geene et al reported that higher postoperative cTnI levels are associated with an increased risk of hospital mortality after cardiac surgery [19]. Selvanayagam et al reported lower postoperative cTnI levels and better left ventricular function after early periods of off-pump surgery, when compared with the on-pump technique [22].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated values of these markers after cardiac surgery are indicative of peri-operative myocardial damage during or after the operation and are associated with increased mortality and morbidity in the short and medium term after cardiac surgery. [23][24][25][26][27][28][29] Lower post-operative CK-MB and cTnI values reported in the Cold Blood group were indicative of a better myocardial protection obtained with cold blood cardioplegia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of 938 consecutive patients undergoing a range of cardiac surgical procedures, Van Geene et al [8] demonstrated that cTnI levels were significant predictors of inhospital mortality and can identify a subgroup of patients with an increased risk for hospital mortality. In addition, Croal et al [9] found that regardless of other potentially confounding variables, including operation complexity, cTnI levels 24 h after surgery are powerful predictors of short-term and long-term mortality.…”
Section: Discussionmentioning
confidence: 99%